Formylpeptide receptors mediate rapid neutrophil mobilization to accelerate wound healing. - Mingyong Liu; Keqiang Chen; Teizo Yoshimura; Ying Liu; Wanghua Gong; Yingying Le; Ji-Liang Gao; Jianhua Zhao; Ji Ming Wang; Aimin Wang (PLoS ONE)
Wound healing is a multi-phased pathophysiological process requiring chemoattractant receptor-dependent accumulation of myeloid cells in the lesion. Two G protein-coupled formylpeptide receptors Fpr1 and Fpr2 mediate rapid neutrophil infiltration in the liver of Listeria-infected mice by sensing pathogen-derived chemotactic ligands. These receptors also recognize host-derived chemotactic peptides in inflammation and injury. Here we report the capacity of Fprs to promote the healing of sterile skin wound in mice by initiating neutrophil infiltration. We found that in normal miceneutrophils rapidly infiltrated the dermis in the wound before the production of neutrophil-specific chemokines by the injured tissue. In contrast, rapid neutrophil infiltration was markedly reduced with delayed wound closure in mice deficient in both Fprs. In addition, we detected Fpr ligand activity that chemoattracted neutrophils into the wound tissue. Our study thus demonstrates that Fprs are critical for normal healing of the sterile skin wound by mediating the first wave of neutrophil infiltration.